The design of scenography that creates different connections between theatrical building and city (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The theater building builds professional and human relationships, which develop a unique transit between this building and the city that houses it. This perspective provided a unique concept of Scenography. The theoretical foundation is centered on the epistemological study that Michel Foucault undertook, recognizing in the 16thcentury the cognitive action of “spatializing knowledge”, which connects the microcosm to the macrocosm. This cognitive “spatialization” will be considered according to the physical and virtual spaces. The virtual will be analyzed using the digital platform, which allows theatrical performances and audiences to be found instreets and squares recreating the containment rules.
Keywords: Theater Building; City; Physical Space; Virtual Space